Room Occupancy Rate of Accommodation Establishments in Davao Region, Philippines: An Empirical Analysis - Cano, Mylen (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was conducted to investigate what models could be developed in analyzing the Room Occupancy Rate (ROR) of accommodation establishments in the Davao Region. This investigation used a quantitative research method utilizing empirical analysis. The statistical tools used were the Bai and Perron multiple structural break test and One Least Squares (OLS) regression. Secondary data was utilized and the sources were from various government agencies and reliable websites. The key findings of this investigation include overall mean of 29.53% for the ROR of accommodation establishments in Davao Region between 2016 and 2022. Results revealed that the presence of three breakpoints happened in January 2019, January 2022 and March 2020. The OLS regression and Augmented Dickey-Fuller (ADF) test result exhibit that the sources and magnitude of the structural breaks are Public Safety with permanent effect, Regime with permanent effect, Earthquake with transitory effect and Health Crisis with permanent effect. The conclusions of this study imply that it just simplifies the actual events occurring in the Davao Region’s Accommodation Industry.